Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1046/j.1523-1747.2002.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between p53 Codon 72 Polymorphism and Susceptibility to Sunburn and Skin Cancer

Abstract: Upregulation of p53 protein induces either growth arrest or apoptosis in response to cellular injury This is signaled from a highly conserved p53 domain between codons 64 and 92, where a functional polymorphism results in either a proline (p53-72P) or an arginine (p53-72R) at codon 72. Preliminary studies suggest that p53-72R may be a risk factor for cervical cancer and, consistent with this, preferential mutation and retention of the p53-72R allele has also been demonstrated in other cancers of squamous cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
89
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 40 publications
4
89
2
1
Order By: Relevance
“…Although inactivating mutations in the tumor suppressor p53 gene are one of the most common genetic changes in human cancers (29 -31), a germ line mutation exists in the p53 gene at codon 72 within the transactivation domain-II that can alter apoptotic rates, cancer incidence, and anti-cancer drug responses (32,33). Interestingly, a relatively rare germ line mutation exists in the p53 gene at a MAPK kinase phosphorylation site near the p53 transactivation domain at Ser-47.…”
Section: Discussionmentioning
confidence: 99%
“…Although inactivating mutations in the tumor suppressor p53 gene are one of the most common genetic changes in human cancers (29 -31), a germ line mutation exists in the p53 gene at codon 72 within the transactivation domain-II that can alter apoptotic rates, cancer incidence, and anti-cancer drug responses (32,33). Interestingly, a relatively rare germ line mutation exists in the p53 gene at a MAPK kinase phosphorylation site near the p53 transactivation domain at Ser-47.…”
Section: Discussionmentioning
confidence: 99%
“…A polymorphism of p53 at codon 72 in exon 4 encoding either proline or arginine has been reported to influence the risk for certain types of cancer, including human papillomavirus (HPV)-associated cervical and nonmelanoma skin cancers (Storey et al, 1998;McGregor et al, 2002;Saranath et al, 2002), and bladder cancer (Soulitzis et al, 2002). This correlation has been proposed to be due to the increased susceptibility of p53 to degradation by HPV E6 when p53 is homozygous for arginine at codon 72 (Storey et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…2 of the online Data Supplement). This polymorphism may play a role in cancer susceptibility (21,22 ) and response to therapy (2 ). Recently, Bonafe et al (23 ) reported that preferential loss of the codon 72P allele in breast tumors of heterozygous patients was associated with a significant decrease in disease-free and overall survival.…”
mentioning
confidence: 99%